2017
DOI: 10.1063/1.5000873
|View full text |Cite
|
Sign up to set email alerts
|

Electrostatic solitary waves in an electron-positron pair plasma with suprathermal electrons

Abstract: The nonlinear propagation of electrostatic solitary waves is studied in a collisionless electronpositron pair plasma consisting of adiabatic cool electrons, mobile cool positrons (or electron holes), hot suprathermal electrons described by a κ distribution, and stationary ions. The linear dispersion relation derived for electrostatic waves demonstrates a weak dependence of the phase speed on physical conditions of positrons in appropriate ranges of parameters. The Sagdeev's pseudopotential approach is used to … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 68 publications
1
7
0
Order By: Relevance
“…Furthermore, it is noticed that in comparison to cylindrical shock waves, the spherical shock wave moves faster. Furthermore, the shock wave amplitude decreases with an increase in the non‐extensive parameter q (non‐extensivity decreases) and cold to hot electron density ratio α , which is in agreement with the results of Danekhar. Because the ions are present in a small fraction and positrons have a long life, the major constituents of astrophysical and space plasma are electrons and positrons.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Furthermore, it is noticed that in comparison to cylindrical shock waves, the spherical shock wave moves faster. Furthermore, the shock wave amplitude decreases with an increase in the non‐extensive parameter q (non‐extensivity decreases) and cold to hot electron density ratio α , which is in agreement with the results of Danekhar. Because the ions are present in a small fraction and positrons have a long life, the major constituents of astrophysical and space plasma are electrons and positrons.…”
Section: Discussionsupporting
confidence: 88%
“…Numerical solution showed that the presence of non‐extensive particles, magnetic field, obliqueness, and temperature of different species have a great effect on the basic features of EASWs. Recently, Danekhar studied the non‐linear electrostatic waves in collisionless plasma consisting of cool positrons and superthermal electrons. Using Sagdeev's pseudopotential method, he investigated the characteristics of electrostatic waves with respect to physical conditions of superthermal electrons and positrons.…”
Section: Introductionmentioning
confidence: 99%
“…[54]). Alternatively, mobile cool positrons (or electron holes), together with suprathermal hot electrons, may support positive polarity electrostatic waves with the propagation speed comparable to the negative polarity electron-acoustic solitons [58].…”
Section: Discussionmentioning
confidence: 99%
“…However, the ion inertia propagates electrostatic waves in a slow-acoustic mode [54]. Thus, mobile positrons (or electron holes) may provide the inertia to have positive polarity in a fast-acoustic mode similar to the negatively polarized electronacoustic solitons [58]. Figure 5 shows the variation of the pseudopotential Ψ(φ) with the normalized potential φ, for different values of the positive normalized beam speed V b (keeping ρ h,c = 1, ρ b,c = 0.008, θ c,h = θ b,h = 0.01, κ = 4.0 and Mach number M = 0.9, all fixed).…”
Section: Nonlinear Electron-acoustic Wave Structuresmentioning
confidence: 99%
“…[ 45 ] The nonlinear feature of electrostatic solitary waves was presented in a collisionless plasma consisting of stationary ions, mobile cool positrons, adiabatic cool electrons and hot κ distribution electrons. [ 46 ] Three‐dimensional modulational instability of electrostatic waves was described in e‐p‐i magnetoplasmas with κ distribution electrons. [ 47 ] Sagdeevs pseudopotential method is used to investigate small and arbitrary amplitude dust acoustic waves in a plasma which is constitute of kappa distributed electrons and ions as well as power law size distribution dust grains.…”
Section: Introductionmentioning
confidence: 99%